Artificial bee colony for the standard cell placement problem. (1st January 2013) - Altwaijry, Najwa; Menai, Mohamed El Bachir
Placement is an important step in the VLSI design process, of which standard cell placement (SCP) is a well-studied problem. The four 'pure' major algorithms for placement include simulated annealing, quadratic placement, min-cut placement, and force-directed placement. The four pure algorithms are inadequate for today's complex problems; hybrid methods are better able to solve the current SCP problem sizes. The objective of this paper is to present a swarm intelligence-based method for SCP. The method used to solve the SCP problem is the artificial bee colony (ABC) algorithm, in conjunction with hMetis, a partitioning package. Our artificial bee colony PLacer tool (abcPL), has been tested on the PEKU benchmark suite. Results obtained show that ABC is a promising approach for solving the SCP problem.